2000
DOI: 10.1046/j.1432-1327.2000.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship and site of binding of polyamine derivatives at the nicotinic acetylcholine receptor

Abstract: Several wasp venoms contain philanthotoxins (PhTXs), natural polyamine amides, which act as noncompetitive inhibitors (NCIs) on the nicotinic acetylcholine receptor (nAChR). Effects of varying the structure of PhTXs and poly(methylene tetramine)s on the binding affinity have been investigated. Using the fluorescent NCI ethidium in a displacement assay K app values of these compounds have been determined. We found that an increase in size of the PhTX's hydrophobic head group significantly increased the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
8

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 36 publications
3
52
0
8
Order By: Relevance
“…nAChR by PhTX-343 have been reported. The noncompetitive nature of philanthotoxin inhibition of nAChR is supported by Bixel et al (2000), who showed that the binding of N 3 -Ph-PhTX-343-Lys to resting (12) 1 M 1.62 Ϯ 0.27 (5) state Torpedo californica nAChR is unaffected by the presence of ␣-BgTX and slightly enhanced by the presence of carbamylcholine. Bixel et al (2001) also showed that binding of a related philanthotoxin, 125 I-MR44, was largely unaffected by either ␣-BgTX or carbamylcholine.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…nAChR by PhTX-343 have been reported. The noncompetitive nature of philanthotoxin inhibition of nAChR is supported by Bixel et al (2000), who showed that the binding of N 3 -Ph-PhTX-343-Lys to resting (12) 1 M 1.62 Ϯ 0.27 (5) state Torpedo californica nAChR is unaffected by the presence of ␣-BgTX and slightly enhanced by the presence of carbamylcholine. Bixel et al (2001) also showed that binding of a related philanthotoxin, 125 I-MR44, was largely unaffected by either ␣-BgTX or carbamylcholine.…”
Section: Discussionmentioning
confidence: 93%
“…1), a structurally close analog of PhTX-433, is one of many synthetic analogs of the natural product Bruce et al, 1990;Benson et al, 1992Benson et al, , 1993Strømgaard et al, 1999Strømgaard et al, , 2000Bixel et al, 2000). It is a potent antagonist of ionotropic glutamate receptors mediating neuromuscular transmission in insects (Eldefrawi et al, 1988;Bruce et al, 1990), of ionotropic glutamate receptors of rat brain (Ragsdale et al, 1989;Jones et al, 1990;Brackley et al, 1993), and of recombinant, ionotropic glutamate receptors from rat (Brackley et al, 1993;Bä hring and Mayer, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic analogues of this polyamine amide, such as PhTX-343, have been shown to noncompetitively antagonize a range of ionotropic receptors (21), including nAChR (22)(23)(24)(25)(26). These low molecular weight compounds have a hydrophobic head group linked to a polyamine tail.…”
mentioning
confidence: 99%
“…We have synthesized a series of polyamine-containing analogues of PhTX-343 in the search for a ligand with high affinity and specificity for Torpedo californica nAChR for photocross-linking studies. This approach resulted in the discovery of a photoactivable compound, MR44, which binds to the nAChR with high affinity (26,29).…”
mentioning
confidence: 99%